Design and Validation of an Instrument to Measure Students’ Interactions and Satisfaction in Undergraduate Chemistry Laboratory Classes - Wei, Jianye; Treagust, David; Mocerino, Mauro; Vishnumolakala, Venkat; Zadnik, Marjan; Lucey, Anthony; Lindsay, E.D. (SPRINGER, 2020)
© 2020, Springer Nature B.V. This paper describes the development, final design and validation of an instrument that measures a range of student interactions and satisfaction in undergraduate chemistry laboratories. Student surveys or conceptual and attitudinal instruments are widely used techniques for collecting relevant information on student learning. However, there is a lack of specific instruments for collecting data on the relationships between social factors and learning. Consequently, this study attempted to fill this gap by introducing an instrument—the Interactions in Undergraduate Laboratory Classes (IULC). The design of the IULC instrument is based on the theory of distributed cognition, meaning that knowledge is not rooted in an individual’s mind, but develops in the process of interacting with the environment. The instrument covers three aspects: (i) frequency of interactions, (ii) satisfaction and (iii) importance of interactions for the specific laboratory. Undergraduate students (N = 204) enrolled in a first-year chemistry course participated in a test case for the instrument and the corresponding data were analysed using different methods for each of the three parts. The factor structure of the data obtained from the first part of the instrument and internal consistency measures are discussed. Among findings captured by the instrument, student-teacher (instructors in the university context) interactions correlated positively with students’ satisfaction levels. Implications and suggestions for the use of the instrument are discussed.